ANALISIS KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) DAN METODE MARKET VALUE ADDED (MVA) (Studi pada PT Japfa Comfeed Indonesia Tbk. dan PT Charoen Pokphand Indonesia Tbk. Di BEI Periode 2009-2011) - Lina Lutfiana (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
The financial performance measurement can be done by various methods. In general, the most widely used is the financial ratio analysis method. Financial ratio analysis method not pay attention the cost of capital, so to overcome this weakness created a method of measuring financial performance by using value-added method, that is economic value added (EVA) and market value added methods (MVA). This study aims to determine the financial performance PT Japfa Comfeed Indonesia Tbk. and PT Charoen Pokphand Indonesia Tbk using economic value added (EVA) and market value added method (MVA), as well as to compare the financial performance of both companies are using the economic value added (EVA) method and of market value added (MVA) method. The research method that used is descriptive method. This study uses quantitative analysis calculations in which there are economic value added (EVA) and market value added (MVA). The data is derived from the consolidated financial statements. The data used to calculate EVA include interest expense, cost of capital, interest rate and stock index SBI. As for the calculation of MVA, the data used is the number of shares outstanding, the stock's closing price and the book value of shares. Keywords : Financial performance, EVA, MVA